Endoplasmic reticulum stress as a novel inducer of hypoxia inducible factor-1 activity: its role in the susceptibility to myocardial ischemia‐reperfusion induced by chronic intermittent hypoxia. (1st May 2016) - Belaidi, Elise; Thomas, Amandine; Bourdier, Guillaume; Moulin, Sophie; Lemarié, Emeline; Levy, Patrick; Pépin, Jean-Louis; Korichneva, Irina; Godin-Ribuot, Diane; Arnaud, Claire
Abstract: Background: Obstructive sleep apnea (OSA) is a highly prevalent disease and a risk factor for myocardial infarction expansion in humans. Intermittent hypoxia (IH) is known to be the most important OSA feature in terms of cardiovascular morbi-mortality. Since ER stress and HIF-1 are known to be involved in cardiomyocyte life or death, this study investigates the role of ER stress on HIF-1 activation in myocardial susceptibility to ischemia‐reperfusion (I/R) induced by IH. Methods: C57Bl6J, HIF-1α +/‐ and their respective control mice were exposed to 14 days of IH (21–5% FiO2, 60 s cycle, 8 h/day). Myocardial inter-organelle calcium exchanges, ER stress and HIF-1 activity were investigated and in vivo I/R was performed to measure infarct size. In additional groups, tauroursodeoxycholic acid (TUDCA, 75 mg·kg ‐ 1 ), an ER stress inhibitor, was administered daily during exposure. Results: In C57Bl6J mice, chronic IH induced an increase in ER-Ca 2 + content, ER stress markers and HIF-1 activity, associated with an enhanced infarct size (33.7 ± 9.4 vs. 61.0 ± 5.6% in N and IH, respectively, p < 0.05). IH failed to increase infarct size in HIF-1α deficient mice (42.4 ± 2.7 and 24.7 ± 3.4% N and IH, respectively). Finally, TUDCA totally abolished the IH-induced increase in HIF-1 activity (1.3 ± 0.04 vs. 0.14 ± 0.02 fold increase in IH vs. IH-TUDCA respectively, p < 0.0001) and in infarct size (55.5 ± 7.6 vs. 49.9 ± 3.0 in N-TUDCA and IH-TUDCA, respectively). Conclusion: This novel regulatory mechanism of HIF-1 activity by ER stress should be considered as a potential diagnostic tool for cardiovascular complications in OSA patients as well as a therapeutic target to limit myocardial ischemic damage.